2020
DOI: 10.3389/fnhum.2020.549966
|View full text |Cite
|
Sign up to set email alerts
|

N-Back Related ERPs Depend on Stimulus Type, Task Structure, Pre-processing, and Lab Factors

Abstract: The N-Back, a common working memory (WM) updating task, is increasingly used in basic and applied psychological research. As such, an increasing number of electroencephalogram (EEG) studies have sought to identify the electrophysiological signatures of N-Back task performance. However, stimulus type, task structure, pre-processing methods, and differences in the laboratory environment, including the EEG recording setup employed, greatly vary across studies, which in turn may introduce inconsistencies in the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 83 publications
1
21
0
Order By: Relevance
“…We hypothesized that ERP amplitude for match and non-match trial types would be more pronounced for verbal compared to spatial stimuli, particularly within approximately 200 to 350 msec post-stimulus (P2, N2, and early P3 range). This was anticipated because of the potential increased processing demand required for semantic and phonological aspects of verbal information compared to spatial location (e.g., Mecklinger and Pfeifer, 1996;Shalchy et al, 2020). We also hypothesized that ERP activity in the P3 range would show similar amplitude across stimulus modalities for the lure trial type, in line with prior studies that have indicated that the P3 re ects domain-general executive control processes.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…We hypothesized that ERP amplitude for match and non-match trial types would be more pronounced for verbal compared to spatial stimuli, particularly within approximately 200 to 350 msec post-stimulus (P2, N2, and early P3 range). This was anticipated because of the potential increased processing demand required for semantic and phonological aspects of verbal information compared to spatial location (e.g., Mecklinger and Pfeifer, 1996;Shalchy et al, 2020). We also hypothesized that ERP activity in the P3 range would show similar amplitude across stimulus modalities for the lure trial type, in line with prior studies that have indicated that the P3 re ects domain-general executive control processes.…”
Section: Introductionsupporting
confidence: 54%
“…One widely used paradigm for studying WM performance is the n-back task. In general, n-back tasks require stimulus encoding and the ongoing short-term maintenance of information, selective attention, discrimination of target and non-target stimuli, ltering of distracting information, and continuous updating of the contents of WM (Postle et al, 2000;Sandrini, Rossini, and Miniussi, 2008;Gevins and Cutillo, 1993;Shalchy et al, 2020). During an n-back task, participants are required to determine if a stimulus presented in a sequence of stimuli is the same or different than a stimulus presented n trials back.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, early responses at ~ 40–150 ms post-stimulus, termed P1 and N1 components, have been reported (Pratt et al 2011 ; Liu et al 2017 ; Zhao et al 2020 ). The N1 and P1 components are thought to reflect early attentional processing and low level features (Hillyard and Anllo-Vento 1998 ; Woodman 2010 ; Pratt et al 2011 ; Hinojosa et al 2015 ; Shalchy et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in WM-load are a significant part of the WM studies. The N-back paradigm is one of the tasks frequently mentioned in WM, which is used to manipulate the high and low cognitive WM-loads [13]. By utilizing the subjective assessment based on different task difficulties under the N-back experiments, it has been found that the tasks with the high-load levels are more suitable for assessing WM capacity [14].…”
Section: Introductionmentioning
confidence: 99%